(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
In the framework of Relevance Theory, this paper discusses the coercion cases imposed by nominal classifiers in Chinese and proposes a translation strategy. The results show that the coercion imposed by nominal classifiers in Chinese appears in the cases of metaphor or metonymy. In these cases, the conflict between procedural semantics and conceptual semantics is always resolved in favor of the procedural one. Therefore, when we translate them from Chinese to Spanish, to get a correct translation, we should find out firstly the procedural semantics of the nominal classifiers and then combine them with the metaphor or metonymy meaning of the nouns generated in coercion contexts.